“The Problem Of Establishing Soviet Power In Armenia According To The Assessment Of The Social And Political Thought Of The Armenian Diaspora (1920-1930s)”, Antelias, 2021, 420 pages, by Khachatur Rostom Stepanyan - Virabyan, Amatuni (ՀՀ ԳԱԱ)
One of the most controversial issues in the Armenian history of the 20th century is the Sovietization of Armenia. It is self-evident how this historical event was evaluated and glorified in the Soviet country during its 70 years of existence. The issue of Sovietization was also addressed by the Diasporan historiographer and memorialist authors, the press, the wider public and political circles, whose comments and assessments were multi-layered and ambiguous depending on their party, ideological, fragmentary approaches and preferences.
Keywords: Հայագիտություն; Հայոց պատմություն; Պատմություն; Հայոց ցեղասպանություն (1915); Հայագիտական ժառանգություն; Հնագիտություն և ազգագրություն; Փիլիսոփայություն և իրավունք; Արվեստ և ճարտարապետություն; Ժողովրդագրություն և կառավարում